Stereoselective Synthesis and Reactions of Secondary Alkyllithium Reagents Functionalized at the 3‐Position1. Issue 9 (12th January 2015) - Moriya, Kohei; Didier, Dorian; Simon, Meike; Hammann, Jeffrey M.; Berionni, Guillaume; Karaghiosoff, Konstantin; Zipse, Hendrik; Mayr, Herbert; Knochel, Paul
Abstract Secondary alkyllithium reagents bearing an OTBS group (TBS=tert‐butyldimethylsilyl) at the 3‐position can be prepared stereoconvergently through an I/Li exchange from a diastereomeric mixture of the corresponding secondary alkyl iodides. These lithium reagents react with a range of electrophiles, including carbon electrophiles, with retention of configuration to yield various 1, 3‐difunctionalized derivatives with good diastereoselectivities. Kinetic studies show that the 3‐siloxy group strongly accelerates the epimerization at the lithium‐substituted carbon atom. This method offers a new way to construct chiral open‐chain molecules with excellent stereoselectivity.